Neuronal ferroptosis after intracerebral hemorrhage - Ren, Siying; Chen, Yue; Wang, Likun; Wu, Guofeng (Frontiers in Molecular Biosciences, 2022)
Ferroptosis is a recently discovered type of cell death caused by the imbalance of intracellular redox metabolism. Ferroptosis is associated with various physiopathological processes, including normal development, ischemic organ damage, neurodegenerative diseases, and immune system activity, and plays a particularly important role in the occurrence and progression of intracerebral hemorrhage (ICH). Many ICH-induced regulators and signaling pathways of ferroptosis have been reported as promising targets for treating ICH. However, the mechanism of secondary neurological impairment after ICH remains unclear, and its relationship with neuronal ferroptosis caused by iron deposition after ICH remains to be elucidated in further research. In this article, we review the definition, characteristics, and inhibition methods of neuronal ferroptosis caused by iron deposition after ICH, and review the biomarkers for ferroptosis.